2021
DOI: 10.3389/fonc.2021.662392
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Clinical Trials Safety Profile of PD-1/PD-L1 Inhibitors Among Patients With Cancer: An Updated Systematic Review and Meta-Analysis

Abstract: BackgroundUnderstanding the safety and adverse event profiles of PD-1/PD-L1 inhibitors is important in guiding cancer immunotherapy. Consequently, we designed this meta-analysis to evaluate the safety of PD-1/PD-L1 inhibitors in clinical trials involving cancer patients.MethodsFour safety indicators comprising treatment-related adverse events, death, discontinuation of therapy and grades 3–5 adverse events were evaluated using the random effect model. The quality of enrolled trials was assessed using the Newca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
(414 reference statements)
0
3
0
Order By: Relevance
“…Basic characteristics of 86 clinical trials included in the study were extracted and shown in Table 1 [ 5 ], [ 22 25 ], [ 26 30 ], [ 31 35 ], [ 36 40 ], [ 41 45 ], [ 46 50 ], [ 51 55 ], [ 56 60 ], [ 61 65 ], [ 66 70 ], [ 71 75 ], [ 76 80 ], [ 81 85 ], [ 86 90 ], [ 91 95 ], [ 96 110 ], [ 111 115 ], [ 116 , 117 ]. 6 clinical trials, including KEYNOTE-021 [ 27 , 28 ], KEYNOTE-189 [ 40 42 ], CheckMate 227 [ 47 , 48 ], JAVELIN Renal 101 [ 51 , 52 ], KEYNOTE-042 [ 61 , 62 ], and CheckMate 067 [ 114 117 ], were repeatedly reported multiple times by different reporters, and only one with the detailed data could be selected for the final analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic characteristics of 86 clinical trials included in the study were extracted and shown in Table 1 [ 5 ], [ 22 25 ], [ 26 30 ], [ 31 35 ], [ 36 40 ], [ 41 45 ], [ 46 50 ], [ 51 55 ], [ 56 60 ], [ 61 65 ], [ 66 70 ], [ 71 75 ], [ 76 80 ], [ 81 85 ], [ 86 90 ], [ 91 95 ], [ 96 110 ], [ 111 115 ], [ 116 , 117 ]. 6 clinical trials, including KEYNOTE-021 [ 27 , 28 ], KEYNOTE-189 [ 40 42 ], CheckMate 227 [ 47 , 48 ], JAVELIN Renal 101 [ 51 , 52 ], KEYNOTE-042 [ 61 , 62 ], and CheckMate 067 [ 114 117 ], were repeatedly reported multiple times by different reporters, and only one with the detailed data could be selected for the final analyses.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of research into the mechanisms of immune escape, PD-1 or PD-L1 inhibitors have reshaped the therapy landscape for cancer by activating the immune system, while also gradually reporting plenty of treatment-related side effects [3]. Although the association between some adverse events and PD-1 or PD-L1 inhibitors has been extensively examined and documented [4][5][6][7][8][9], many toxicities remain unexplored, including skin toxicities [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among all immune checkpoints, the PD-1/PD-L1 signaling pathway has received increasing attention due to its proven outstanding effectiveness as an immune therapeutic target in a wide range of tumors, including bladder cancer, lung cancer, and pancreatic cancer [6][7][8]. However, the response to anti-PD-1/PD-L1 therapy differs among different malignancies and patients, and multiple mechanisms have been found to hinder tumor immunity during tumorigenesis [9][10][11]. This finding urges current researchers to evaluate the underlying mechanisms by which the PD-1/PD-L1 pathway is regulated in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%